2014
DOI: 10.15253/2175-6783.2014000100020
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the concept of nursing educational technology applied to the patient

Abstract: Analysis of the concept of nursing educational technology applied to the patient Análise do conceito de tecnologia educacional em enfermagem aplicada ao paciente Análisis del concepto de tecnología educacional en enfermería aplicada al paciente

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 18 publications
0
22
0
9
Order By: Relevance
“…Educational materials evaluated by content instruments in the health area should aim at facilitating the work of health professionals in orienting and educating patients and family (13) . Furthermore, they must aim at promoting healthy, ensuring the effectiveness of care for the target population.…”
Section: Discussionmentioning
confidence: 99%
“…Educational materials evaluated by content instruments in the health area should aim at facilitating the work of health professionals in orienting and educating patients and family (13) . Furthermore, they must aim at promoting healthy, ensuring the effectiveness of care for the target population.…”
Section: Discussionmentioning
confidence: 99%
“…34 To foster the relationship between theory and practice, it is also possible to invest in the use of educational technologies and simulation. 6,38 In this sense, considering that the increasing technological evolution brings possibilities of using new resources in healthcare and teaching practices, 6 it is believed that greater investments are needed for implementing educational technologies in teaching nursing management. Only three studies were identified with this focus in this review.…”
Section: Discussionmentioning
confidence: 99%
“…5 In this historical moment the emergence of technological resources such as tools to improve teaching in health and nursing can also be highlighted. 6 Due to these changes and the complexity of health problems in Brazil, higher education institutions have been building a pedagogical model that considers the social, economic and cultural dimensions of the population. In addition to the technical knowledge of each action area, future professionals need to be equipped to act in response to the population's health needs in an interdisciplinary way in order to enable comprehensive care.…”
Section: Introductionmentioning
confidence: 99%
“…One of the goals is to facilitate communication. The increasing technological evolution expresses new possibilities of use of these materials in the practices of care and education (15) . In this sense, the parameter guide has been used as support material in the training of new nurses for the application of the Patient Classification System in a qualified manner.…”
Section: Discussionmentioning
confidence: 99%